Pelatihan Public Speaking melalui Komunikasi Strategi Dakwah dalam Pengembangan Pengetahuan dan Ketrampilan Berpidato - Meifilina, Andiwi (Universitas Islam Balitar, 2021)
The use of speaking skills continues to develop according to the times and changes in art and models that occur in society.The ability of public speaking for women is very important, especially in understanding rhetoric and communication strategies in preaching such as speech techniques.Fatayat Nahdlatul 'Ulama is an Islamic youth organization, which is one of the autonomous institutions within the Nahdlatul 'Ulama. The objectives of this activity are (1) to increase knowledge, understanding. The place for the implementation of the community service training program at Fatayat NU in Papungan Village, Kanigoro District, Blitar Regency. The method used includes the provision of material, including the provision of material, training, distribution of questionnaires and evaluation. The results of community service activities showed that the satisfaction of community service activities held by FISIPOL, Balitar Islamic University, the results of the questionnaire were 62.8% and 37.2% agreed. The expectations of participants from the results of the questionnaire, namely 57.7% and 42.3% agreed. Personnel/members of the community service activity team provide services according to the needs of participants with the results of the questionnaire as much as 55.9% and 44.1% agree. In every complaint/question/problem submitted, it is followed up properly by the resource persons/members involved with the results of the questionnaire as many as 60.5% and 39.5% agreeing and if this activity is held again.